THE ROLE OF UTTERANCE LENGTH AND WORKING MEMORY CAPACITY ON SECOND LANGUAGE (L2) SPANISH LISTENING COMPREHENSION - Kamath, Soumya (East Carolina University, 2022)
This study aims to understand the factors that influence listening success in acquiring Spanish as a second language (L2) so that educators in the future can implement new strategies that will allow their students to improve their listening comprehension skills. Several variables have been posited to influence listening comprehension in a second language (L2), such as factors related to the listener (e.g., working memory capacity) and the aural text (e.g., length of utterance) (Bloomfield et al., 2010). However, there is a dearth of research that statistically explores how much of an effect these variables have on L2 listening comprehension (Vandergrift & Goh, 2012). As such, the primary purpose of this study was to investigate how the variables of working memory capacity (WMC) and length of utterance predict the listening comprehension of L2 Spanish learners when processing native-Spanish speech. Data was collected within the population of native English-speaking learners of L2 Spanish enrolled in upper-level Spanish courses at the university level. Data was pooled from two different tests that assess (1) listening comprehension (a recording of 20 short and 20 long sentences) and (2) working memory capacity (collected from a WMC test called Shapebuilder). The results from this study will help future Spanish educators understand the variables that play a role in listening ability and implement better teaching strategies to improve their students’ listening comprehension skills.
Keywords: working memory, listening comprehension, second language acquisition